Legal Regulations on Health Services and Suitable Food for Prisoners in Class IIa Pancur Batu Correctional Institution - Donni Sinurat; Fitria Ramadhani Siregar; Hasdiana Juwita Bintang (CERED Indonesia Institute, 2025)
This study examines the effectiveness of fulfilling the rights to healthcare services and adequate food provision at the Class IIA Pancur Batu Correctional Institution amid the regulatory transition during the 2024–2025 period. Employing a juridical-empirical research method with statutory, case, and comparative approaches, the study analyzes the harmonization between the mandates of Law Number 22 of 2022 and Minister of Immigration and Corrections Regulation Number 1 of 2025 and the State’s fiscal capacity. The findings reveal a disparity between normative expectations (das Sollen) and operational realities (das Sein). Although prison management demonstrates procedural compliance through the implementation of Standard Operating Procedures (SOPs), food security innovations, and financial digitalization, the substantive effectiveness of service delivery remains constrained by structural barriers. These obstacles include budget limitations under the Standard Input Costs (SBM), food price volatility, and demographic pressures resulting from overcrowding, which heighten health risks. A comparison with the Nelson Mandela Rules confirms gaps in meeting the standards of wholesome food quality and the principle of equivalence of care in healthcare provision. Accordingly, institutional strengthening strategies are required, including budget rationalization, optimization of telemedicine services, and integration of prison healthcare into the national social security system to ensure the protection of inmates’ fundamental rights.